2021
DOI: 10.1108/ijhma-07-2020-0090
|View full text |Cite
|
Sign up to set email alerts
|

On the link between policy uncertainty and housing permits: asymmetric evidence from state-level data in the USA

Abstract: Purpose The purpose of this study is to assess the symmetric and asymmetric impact of a measure of policy uncertainty on house permits issued in each state of the USA. Design/methodology/approach To assess the symmetric effects, the authors use Pesaran et al.’s (2001) linear autoregressive distributed lag (ARDL) approach to error-correction modeling. To assess the asymmetric effects, they rely upon Shin et al.’s (2014) nonlinear ARDL approach to error-correction modeling. Both approaches have the advantage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…(2019) also suggests that the relationship is stronger following the structural changes caused by the GFC of 2007. Notably, uncertainty also negatively impacts housing starts and permits as investors and developers adopt more cautious approaches to spending (Bahaman-Oskooee et al ., 2021; Christou et al ., 2019; Nguyen Thanh et al ., 2020). However, Strobel et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2019) also suggests that the relationship is stronger following the structural changes caused by the GFC of 2007. Notably, uncertainty also negatively impacts housing starts and permits as investors and developers adopt more cautious approaches to spending (Bahaman-Oskooee et al ., 2021; Christou et al ., 2019; Nguyen Thanh et al ., 2020). However, Strobel et al .…”
Section: Resultsmentioning
confidence: 99%
“…A time-varying analysis of this relationship by Christou et al (2019) also suggests that the relationship is stronger following the structural changes caused by the GFC of 2007. Notably, uncertainty also negatively impacts housing starts and permits as investors and developers adopt more cautious approaches to spending (Bahaman-Oskooee et al, 2021;Christou et al, 2019;Nguyen Thanh et al, 2020). However, Strobel et al (2020) reported contrary evidence suggesting that uncertainty shocks affect only housing prices but not investment volumes.…”
Section: 7mentioning
confidence: 99%
“…The deviation due to shocks is not reverting to establish an equilibrium relationship. In addition, the joint F-statistic is tested for the validity of the model if the value is greater than the upper bound, even if the variables are a mix of I∼(0) and I∼(1) (Bahaman-oskooee et al , 2020; Aliefendioğlu et al , 2021).…”
Section: Methodsmentioning
confidence: 99%
“…However, there are several reasons to support that this a restrictive assumption. First, the impact of policy uncertainty on housing production is asymmetric (Bahmani-Oskooee et al , 2021). As policy uncertainty is significantly related with the direction of monetary policy actions, an expansionary policy would impact housing permits differently than contractionary policy.…”
Section: The Models and The Methodsmentioning
confidence: 99%